2014
DOI: 10.2355/isijinternational.54.920
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nano/ultrafine Grain Structure in a Ti-modified 201L Stainless Steel through Martensite Thermomechanical Treatment

Abstract: The formation of nano/ultrafine grain structure in a Ti-modified 201L austenitic stainless steel using the martensite thermomechanical treatment was investigated. Effects of Ti micro-alloy addition on the formation of strain-induced martensite (SIM) during cold rolling and austenite reversion during subsequent annealing were studied. The results showed that the nano-grained Ti-modified 201L steel with the average grain size of 45 nm possessed the yield strength of 1 000 MPa, ultimate tensile strength of 1 330 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For 201 and 201L grades, the temperature of 850 • C has been found to be an adequate reversion annealing temperature resulting in complete reversion within 30 s and in the finest GS [15,16]. Kisko et al [27] obtained high tensile elongations (softened structure) in a 60% cold-rolled 201 ASS after 15 s at 800 • C. Sadeghpour et al [69] found that in a 201L + 0.12Ti steel, the reversion rate depends on temperature and holding time, so that the reversion seemed to be diffusion controlled. The temperature of 900 • C was convenient for the reversion within a soaking time of 60 s.…”
Section: Temperature Range For Reversionmentioning
confidence: 99%
“…For 201 and 201L grades, the temperature of 850 • C has been found to be an adequate reversion annealing temperature resulting in complete reversion within 30 s and in the finest GS [15,16]. Kisko et al [27] obtained high tensile elongations (softened structure) in a 60% cold-rolled 201 ASS after 15 s at 800 • C. Sadeghpour et al [69] found that in a 201L + 0.12Ti steel, the reversion rate depends on temperature and holding time, so that the reversion seemed to be diffusion controlled. The temperature of 900 • C was convenient for the reversion within a soaking time of 60 s.…”
Section: Temperature Range For Reversionmentioning
confidence: 99%